2017
DOI: 10.3389/fnagi.2017.00340
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Vulnerability in Aging May Be Modulated by Education and Reserve in Healthy People

Abstract: Aging is related to a deterioration of cognitive performance and to multiple alterations in the brain. Even before the beginning of a noticeable cognitive decline, the framework which holds cognitive function experiences these alterations. From a system-vulnerability point of view of cognition, the deterioration associated with age would be the collection of repercussions during a life. Brain function and structure are modified in a multidimensional way, which could concern different aspects like structural in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 74 publications
2
16
0
2
Order By: Relevance
“…This result is consistent with studies which reported higher CR in individuals with better overall cognitive efficiency assessed using screening methods (MoCA, Mini-Mental State Examination -MMSE) (Kang et al, 2018), and in subjects with higher abilities in various cognitive domains, e.g., memory (Frankenmolen et al, 2018), as well as visuospatial and executive functions (Roldán-Tapia et al, 2012;Roldán-Tapia et al, 2017). This positive association was found even though the studies applied a variety of CR indicators, such as isolated factors, e.g., leisure activity (Mella et al, 2017), years of education (Farfel et al, 2013;Roldán-Tapia et al, 2017), professional activity (Adam et al, 2013), intellectual and physical activity (Blondell et al, 2014;Cheng, 2016), community involvement (Amieva et al, 2010;Di Napoli et al, 2014;James, Wilson, Barnes, & Bennett, 2011;Scarmeas, & Stern, 2003), or indexes or summary scores acquired in various questionnaires (Grotz et al, 2017;Nucci et al, 2012;Opdebeeck et al, 2016;Pinto & Tandel, 2016). Furthermore, lower level of CR is associated with lower cognitive efficiency in healthy adults (Corral et al, 2006).…”
Section: Predictors Of Cognitive Performancesupporting
confidence: 90%
See 1 more Smart Citation
“…This result is consistent with studies which reported higher CR in individuals with better overall cognitive efficiency assessed using screening methods (MoCA, Mini-Mental State Examination -MMSE) (Kang et al, 2018), and in subjects with higher abilities in various cognitive domains, e.g., memory (Frankenmolen et al, 2018), as well as visuospatial and executive functions (Roldán-Tapia et al, 2012;Roldán-Tapia et al, 2017). This positive association was found even though the studies applied a variety of CR indicators, such as isolated factors, e.g., leisure activity (Mella et al, 2017), years of education (Farfel et al, 2013;Roldán-Tapia et al, 2017), professional activity (Adam et al, 2013), intellectual and physical activity (Blondell et al, 2014;Cheng, 2016), community involvement (Amieva et al, 2010;Di Napoli et al, 2014;James, Wilson, Barnes, & Bennett, 2011;Scarmeas, & Stern, 2003), or indexes or summary scores acquired in various questionnaires (Grotz et al, 2017;Nucci et al, 2012;Opdebeeck et al, 2016;Pinto & Tandel, 2016). Furthermore, lower level of CR is associated with lower cognitive efficiency in healthy adults (Corral et al, 2006).…”
Section: Predictors Of Cognitive Performancesupporting
confidence: 90%
“…The level of CR results from knowledge and skills acquired over the lifespan. Higher CR is determined by higher education level, greater intensity and quality of physical, occupational, social and cognitive activity (Nucci, Mapelli, & Mondini, 2012;Roldán-Tapia, Cánovas, León, & García-Garcia, 2017;Steffener & Stern, 2012;Stern, 2003Stern, , 2009Tucker & Stern, 2011), multilingualism (Schweizer, Ware, Fischer, Craik, & Bialystok, 2012), good social support (Amieva et al, 2010), and intellectual involvement (Adam, Bonsang, Grotz, & Perelman, 2013;Mella, Grob, Döll, Ghisletta, & de Ribaupierre, 2017). CR is adversely affected by interrelated factors such as depression (Butters et al, 2008), poor education, loneliness and sense of isolation, lack of social support (Di Napoli, Wu, & Scogin, 2014), lack of both cognitive stimulation and physical activity as well as metabolic syndromes (Middleton & Yaffe, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the results of another study performed by León et al [61], where the CRS score was related to Rey-Osterrieth Complex Figure short-term-recall (partial ŋ 2 = 0.32 p = 0.002) and long-term-recall (partial ŋ 2 = 0.3, p = 0.003), but not with attention (p = 0.287, no effect size reported) and working memory (p = 0.47, no effect size reported). Roldan-Tapia et al [62] found that inhibition was significantly associated with CRS (β = 0.49; p = 0.007; r = 0.23), but not with other executive functions. No significant correlation was found between the CRS and perception of cognitive status (r = -0.16, no significance value reported) in a study performed by León et al [30].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, our study underlines the importance of considering education in the interpretation of the performance in executive tools [68]. Higher education levels seem to increase the contact with the evaluation contexts and to contribute to cognitive reserve, exerting a protective effect on the decline associated with healthy aging in EF [69]. Importantly, despite the influence of education, the discriminative power of this tool in the detection of EF deficits in MCI and in their differentiation from those of AD patients remains after accounting for this variable.…”
Section: Discussionmentioning
confidence: 99%